High-resolution core scanning data (X-ray fluorescence and computed tomography) in dated sediment core from lake Santa Maria del Oro (Nayarit, Mexico) - Marttiina V Rantala; Isabel Israde-Alcántara; Reza Safaierad; Wojciech Tylmann; Gilles Lepoint; Pierre Francus; John P Smol; Carsten Meyer-Jacob; Christopher Grooms; Nadine Mattielli; Sarah Metcalfe; Paweł Etmański; et al. (PANGAEA, 2025)
This dataset comprises high-resolution biogeochemical data for a sediment sequence (LSMo22-1) from lake Santa Maria del Oro (Nayarit, Mexico). The data were used to explore connections between lake carbon cycling and related ecosystem processes under natural and anthropogenic environmental change over the past four centuries. The sediment core (97 cm in length) was retrieved with a Uwitec corer near the middle of the lake basin (water depth >50 m) in April 2022. Prior to sediment sectioning, the core was analysed with Itrax X-ray fluorescence core scanning and X-ray computed tomography with 500 microns step size. The scan data are provided from the sediment surface down to the depth of 34.15 cm, covering a time period from 2022 to around 1650. Age estimates for each sediment section have been calculated based on radiolead (Pb-210) dating of the surface sediment sections and three radiocarbon (C-14) measurements. Elemental intensities have been centered log-ratio (clr) transformed and all elemental data have been min-max normalized.
In: Rantala, MV et al. (2025): Four centuries of multiproxy biogeochemical and diatom assemblage data in the sediments of lakes Santa Maria del Oro and Teremendo, central Mexico [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.972744